Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $a,b,c>0$ and $a+b+c=3$. Prove that: $$P=\frac{{a}^{2}}{\sqrt{{b}^{3}+1}}+ \frac { { b }^{ 2 } }{ \sqrt{ { c }^{ 3 }+1 } }+\frac{{c}^{2}}{\sqrt{{a}^{3}+1}}\geq \frac{3\sqrt{2}}{2}$$

share|cite|improve this question
i 've repaired aldready – LevanDokite Sep 27 '12 at 8:20
Expanding on Avatar's comment: If none of the answers you received so far on this site are satisfactory to you, maybe you should stop asking questions here... – Dennis Gulko Sep 27 '12 at 8:28
@anmaylamgiau: You asked 7 questions on this site. You did not accept any of the answers that you got, which means that you are not satisfied with with any of them, is that correct? – Dennis Gulko Sep 27 '12 at 8:46
1 *When you have decided which answer is the most helpful to you, mark it as the accepted answer by clicking on the check box outline to the left of the answer. * – draks ... Sep 27 '12 at 9:09
Ok I have just clicking on the check box outline of all my questions :D thanks you so much – LevanDokite Sep 27 '12 at 9:13
up vote 1 down vote accepted

This is going to be long so let's start

First, divide both sides by $\sqrt{2}$ and notice that by AM-GM $$\sqrt{2(a^3+1)}\leq \frac{a^3+3}{2}.$$ Similarly we proceed for the other variables and we find that $$P\geq 2\left(\frac{a^2}{b^3+3}+\frac{b^2}{c^3+3}+\frac{c^2}{a^3+3}\right)=2\left(\frac{a^4}{a^2b^3+3a^2}+\frac{b^4}{b^2c^3+3b^2}+\frac{c^4}{c^2a^3+3a^2}\right).\tag{1}$$

It is therefore sufficient to prove $$\left(\frac{a^4}{a^2b^3+3a^2}+\frac{b^4}{b^2c^3+3b^2}+\frac{c^4}{c^2a^3+3a^2}\right)\geq\frac34.\tag{2}$$

Use Cauchy Schwarz on the LHS of $(2)$ to find that $$\left(\frac{a^4}{a^2b^3+3a^2}+\frac{b^4}{b^2c^3+3b^2}+\frac{c^4}{c^2a^3+3a^2}\right)\geq\frac{(a^2+b^2+c^2)^2}{a^2b^3+b^2c^3+c^2a^3+3(a^2+b^2+c^2)}.\tag{3}$$

Again, it is sufficient to prove

$$4(a^2+b^2+c^2)^2\geq 3(a^2b^3+b^2c^3+c^2a^3)+9(a^2+b^2+c^2).\tag{4}$$

Now, since we may assume without loss of generality that $(b-a)(b-c)\leq 0$, the following is true

$$\begin{split}a^{3}c^{2}+b^{3}a^{2}+c^{3}b^{2}&=a^{3}b^{2}+bc^{2}a^{2}+c^{3}b^{2}+a^{2}(b^{2}-c^{2})(b-a)\\&\leq a^{3}b^{2}+bc^{2}a^{2}+c^{3}b^{2}= ba^{2}\left(ab+\frac{1}{2}c^{2}\right)+bc^{2}\left(bc+\frac{1}{2}a^{2}\right)\\&\leq\frac{ba^{2}(a^{2}+b^{2}+c^{2})}{2}+\frac{bc^{2}(a^{2}+b^{2}+c^{2})}{2}\\&=\frac{a^{2}+b^{2}+c^{2}}{2\sqrt{2}}\sqrt{2b^{2}(a^{2}+c^{2})(a^{2}+c^{2})}\\&\leq\frac{a^{2}+b^{2}+c^{2}}{2\sqrt{2}}\sqrt{\left(\frac{2(a^{2}+b^{2}+c^{2})}{3}\right)^{3}}=3\sqrt{\left(\frac{a^{2}+b^{2}+c^{2}}{3}\right)^{5}},\end{split}\tag{5}$$ it suffices to prove

$$4(a^{2}+b^{2}+c^{2})^{2}\geq 9\sqrt{\left(\frac{a^{2}+b^{2}+c^{2}}{3}\right)^{5}}+9(a^{2}+b^{2}+c^{2})\tag{6}.$$

Set $$w:=\sqrt{\frac{a^{2}+b^{2}+c^{2}}{3}}\tag{7}.$$ By AM-QM, it immediately follows that $$w\geq \frac{a+b+c}{3}=1,$$ moreover, since $$(a+b+c)^2>a^2+b^2+c^2,$$ we also have $$\sqrt 3>w.$$ Rewrite $(6)$ using the parameter $w$ to obtain that our claim is equivalent to prove that $$4w^{4}\geq w^{5}+3w^{2}\Leftrightarrow w^{2}(w-1)(3+3w-w^{2})\geq 0\tag{8}.$$ This last assertion follows using our bounds on $w$, and therefore the proof is complete.

The equality case occurs when $a=b=c=1.$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.